Elementary Education in India A Review of Research - Murthy, C.G. Venkatesha; Ramchand, Mythili (INDIAN EDUCATIONAL REVIEW, 2020)
Elementary education in India has faced the challenges of access, retention, equity and providing quality education to children. Research in elementary education in India has focused on these aspects. The paper first highlights the international perspectives on elementary education. It then reviews Indian studies conducted after 2000 under 10 sections: Access and enrolment, retention and dropout, teaching-learning process, learning achievement, Education of the socially disadvantaged, availability of teachers, their dispositions and training, learning resources including textual materials and ICT, community participation, infrastructure, resources and grants, and policies and their implementation. Each section summarises the research trends, gaps and offers suggestions for future research. It also describes in detail an empirical analysis of more than 400 researches conducted for award of various degrees as well as research papers or reports. The review recommends that future research should prominently focus on in-depth study of various issues as recommended by the National Education Policy, 2020 by adopting qualitative methodology.